2023
DOI: 10.1002/aenm.202302252
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Binary All‐Polymer Solar Cells with Efficiency Over 18.3% Enabled by Tuning Phase Transition Kinetics

Pengqing Bi,
Tao Zhang,
Yong Cui
et al.

Abstract: All‐polymer solar cells (All‐PSCs) are considered to be the most promising candidates for realizing efficient and stable organic solar cells (OSCs). However, the challenge of controlling morphology has hindered the performance of All‐PSCs. Compared to small molecule acceptors, polymer acceptors play a more crucial role in obtaining an ideal morphology for All‐PSCs. The molecular weight of polymer acceptors is one of the key factors determining the morphological and mechanical properties as well as the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…PTVT-T:BTP-eC9 transport to electrodes. 36 In addition, to further assess the charge carrier transport abilities in the PT:BTP-eC9 blend lms, the space charge limited current (SCLC) method was employed to determine the hole (m h ) and electron (m e ) mobilities of the devices. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTVT-T:BTP-eC9 transport to electrodes. 36 In addition, to further assess the charge carrier transport abilities in the PT:BTP-eC9 blend lms, the space charge limited current (SCLC) method was employed to determine the hole (m h ) and electron (m e ) mobilities of the devices. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The shortest charge carrier extraction time and the longest τ of the PT-CN:BTP-eC9 based device suppress the charge carrier recombination and facilitate charge carriers to transport to electrodes. 36 In addition, to further assess the charge carrier transport abilities in the PT:BTP-eC9 blend films, the space charge limited current (SCLC) method was employed to determine the hole ( μ h ) and electron ( μ e ) mobilities of the devices. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting material (PM6- b -PYIT) ( Figure 1D ) yielded the most efficient CBC-based SC-OSCs to date (14.9% PCE). In terms of peak efficiency, state-of-the-art binary polymer:NFA (>19%) (Liu K. et al, 2023 ; Wang et al, 2023 ) and all-polymer OSCs (>18%) (Bi et al, 2023 ) still outperform SC-OSCs. However, CBC-based solar cells are quickly catching up and show untapped potential (Li et al, 2021 ; Wu et al, 2021 , 2022 ; Cheng et al, 2023 ; Zheng et al, 2023 ).…”
Section: Conjugated Block Copolymersmentioning
confidence: 99%
“…This approach is thus very attractive for CBC synthesis, in particular since PM6 (or a derivative thereof) is applied as the D part for some of the best-performing CBCs to date. Bi et al ( 2023 ) investigated the impact of the molar mass of the polymer acceptor in PM6:PYIT all-polymer solar cells. Their findings revealed a substantial influence of the A polymer's length on the aggregation behavior and overall performance of the polymer blend.…”
Section: Pathways To Enhanced Control Over the Cbc Structurementioning
confidence: 99%
“…Organic heterojunctions, which consist of a mixture of an electron donor and an electron acceptor, are commonly used as functional layers in most high-performance polymer solar cells (PSCs). For such a system, one of the features is the presence of a large number of donor/acceptor (D/A) interfaces, which not only promotes the dissociation of strongly bound excitons into weakly bound interface charge-transfer (CT) states (or free charges) but also enriches the photophysical processes. For instance, under the measurement of ultrafast and highly sensitive technologies, additional weak absorption signals, which appear well below the optical gap of the donor and acceptor, have been successively observed in different D/A systems. Several potential mechanisms, such as doping, defect, and polaron-related absorption, have been proposed to explain the origin of these signals. In recent years, more works have demonstrated that the weak absorption signal also comes from direct CT absorption at D/A interfaces. , In other words, a bound CT state can be generated at the D/A interface without undergoing a conventional process, where electrons in the exciton transfer from the donor to the acceptor.…”
Section: Introductionmentioning
confidence: 99%